Percepatan Waktu Pelaksanaan Proyek Dengan Metode CPM Dan Aplikasi Program Linier Pada Proyek Rehabilitasi Daerah Irigasi Sidorejo Kabupaten Grobogan - (Jurusan Teknik Sipil Politeknik Negeri Semarang), Dadiyono Amat Pawiro (Teknis, 2014)
Execution of a construction project requires a systematic and well-planned scheduling so that the project can be run in accordance with the plans that have been planned. Unfavorable scheduling system can cause the project to be inefficient. Execution of a construction project often needs to accelerate the duration of the project which resulted in the addition of indirect costs. Every effort to expedite the implementation of the project in general will result in increased project costs. By increasing the working hours can speed execution time, but the cost for that would be more expensive. This provides the necessary conditions so that the business dilemma that the project can be completed with optimum cost and time. Cost-time optimization needs to be done to determine which activities should be accelerated and how the duration of the acceleration due to the acceleration that the incremental cost to a minimum. The intention and purpose of this research is to accelerate the execution time by using the method of CPM overtime, so we get the optimal time and cost. This research method by forming a linear equation of the trajectory of the crisis and then analyzed by linier program LINDO. The results Â on the Rehabilitation Project DI Sidorejo are is 161 days with optimum total cost of Rp 3,733,520,010.00, resulting in cost efficiency of Rp 10,480,990.00 of the normal cost Rp 3,744,001,000.00 or 0.28%, project duration of 19 days sooner than the normal time of 180 days or 10.56% Cost efficiency occurs because the direct cost necessary to speed up the project implementation period is smaller than the reduction in overhead costs.Keywords: acceleration, time, execution, Â project.